Digital Forensic Practices and Methodologies for AI Speaker Ecosystems - Jo, Wooyeon; Shin, Yeonghun; Kim, Hyungchan; Yoo, Dongkyun; Kim, Donghyun; Kang, Cheulhoon; Jin, Jongmin; Oh, Jungkyung; Na, B.; Shon, Taeshik (Digital Investigation, 2019)
Various Internet of Things (IoT) devices, such as AI speakers, are being released with different functions to improve user convenience and better life. An AI speaker ecosystem is a cloud-based IoT system built around an AI speaker and IoT devices. In the near future, citizens in whole countries worldwide will be helped in real life when AI-equipped devices are deployed in their homes. Typically, because AI speakers are always operating, they can be used to provide vital evidence for digital forensics; however, privacy issues may arise. AI speakers have provided evidence of murders in the United States and Mexico and are being released without specific regulatory guidelines. In this study, we propose five digital forensic analysis methods for four AI speaker models from different manufacturers released in the Republic of Korea. The five proposed methods are applied to all the AI speaker models, and the results are presented in the Appendix. In particular, we developed a forensic tool for collecting user command history for NAVER Clova.
Keywords: Digital forensic analysis; Forensic tools; Internet of Things (IOT); KT GiGA genie; NAVER Clova; Regulatory guidelines; Republic of Korea; SKT NUGU; AI speaker; Cloud; Ecosystem; Internet of things; KAKAO i; KT GiGA genie; NAVER Clova; SKT NUGU